Development of a traditional game-based guidance and counseling module to promote prosocial behavior in students - Wildawati Wildawati; Abdullah Sinring; Abdullah Pandang; Suciani Latif (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study aims to: (i) describe the need of developing a guidance and counseling module based on traditional games to promote prosocial behavior in students of SDN (State Elementary School) 86 Longi; (ii) describe the prototype of a guidance and counseling module based on traditional games to promote prosocial behavior in students of SDN 86 Longi;and (iii) examine the acceptability of the development of a guidance and counseling module based on traditional games to promote prosocial behavior in students of SDN 86 Longi. This study used the Research and Development approach that was developed by Borg and Gall and consisted of seven stages. The subjects of this study were eight students of SDN 86 Longi. The data of this study were collected through interviews, observations, and questionnaires. Meanwhile, the data were analyzed both qualitatively and quantitatively. Results showed that (1) developing a traditional game-based guidance and counseling module for SDN 86 Longi students was very necessary; (ii) the prototype of the traditional game-based guidance and counseling module consisted of a module for students, teacherâ€™s manuals and worksheets; (iii) the acceptability of the traditional game-based guidance and counseling module was considered valid and usable based on the results of the utility, feasibility, accuracy, content and small group testing.Â